Forever Vital: Redefining Age, Well-being, and Quality of Life - Shah Ali (Magyar Gerontológia, 2025)
Pakistan is entering a demographic transition with one of the fastest-growing ageing populations in South Asia. Despite this shift, ageing in Pakistan is predominantly framed through a medical and welfare lens, emphasizing dependency, decline, and family-based care.